Towards transformative innovation ecosystems: a systemic approach to responsible innovation - Philipp Neudert; Mareike Smolka; Stefan Böschen (Journal of Responsible Innovation)
To address societal challenges, innovators committed to responsibility need to find ways to break away from unsustainable, or otherwise undesirable, path-dependencies in sociotechnical regimes. Such path-breaking innovation should not come at the expense of socioethical desirability. The emerging literature on responsible innovation ecosystems has focused on socioethical desirability but has neglected sociotechnical viability beyond a protected niche. Drawing on theoretical insights and concepts from the literature on Responsible Innovation, innovation ecosystems, and transition studies, we distinguish four types of ecosystems along the axes of desirability and viability and discuss examples of these types. We introduce the concept of transformative innovation ecosystems to refer to a type of ecosystem that combines desirability with viability. The concept is developed by bringing theoretical perspectives into conversation with empirical insights from the high-tech research and innovation cluster NeuroSys, which aims to create an ecosystem around brain-inspired computing.